Photography after conceptual art - Costello, Diarmuid; Iversen, Margaret (Oxford : Wiley-Blackwell, 2010)
- Auto-maticity: Ruscha and performative photography / Margaret Iversen##- Ed Ruscha, Heidegger, and deadpan photography / Aron Vinegar##- Subject, object, mimesis: the aesthetic world of the Bechers' photography / Sarah E. James##- Exit ghost: Douglas Huebler's face value / Gordon Hughes##- Productive misunderstandings: interpreting Mel Bochner's theory of photography / Luke Skrebowski##- Roni Horn's Icelandic encyclopedia / Mark Godfrey##- Thomas Demand, Jeff Wall and Sherrie Levine: deforming 'pictures' / Tamara Trodd##- Almost Merovingian: on Jeff Wall's relation to nearly everything / Wolfgang Bruckle##- Morning cleaning: Jeff Wall and The large glass / Christine Conley.
Includes bibliographical references and index.
boek